Reuse of building components – Assessment system to support decisions in indoor re-layout interventions - Giancarlo Paganin; Cinzia Maria Luisa Talamo; Nazly Atta; Elisa Tinelli (Agathón)
Compared to other industrial fields, the construction sector, although encouraged by a framework of international policies that push towards spreading circular economy principles, still needs to adopt new ‘closed cycle’ resource management models. Among the barriers that hinder this transition is the limited availability of tools and methods to determine the overall outcomes of circularity actions. Although metrics to evaluate the degree of circularity of processes and products are currently available, tools that allow the evaluation of the environmental benefits achievable through the reuse of products and systems have yet to be widespread. The paper proposes a simplified method for quantifying the environmental benefits that can derive from the reuse practices of building components in building re-layout projects.